Atypical Perinuclear Anti-Neutrophil Cytoplasmic Antibodies in Ocular Inflammatory Diseases. (18th August 2019) - Ebrahimiadib, Nazanin; Ma, Lina; Modjtahedi, Bobeck S.; Davoudi, Samaneh; Rahmani, Safa; Syeda, Sarah; Stephenson, Andrew; Foster, Charles Stephen
ABSTRACT: Purpose : To characterize the clinical features of patients with ocular inflammatory diseases (OID) who tested positive for atypical perinuclear anti-neutrophil cytoplasmic antibodies (P-ANCA). Methods : Retrospective case series of patients with OID seen at the Massachusetts Eye Research and Surgery Institute (MERSI) from April 2014 to April 2016. Results : 813 patients were tested for ANCA with 34 patients (4%) being positive for atypical P-ANCA. Among those with positive atypical P-ANCA, the most frequent diagnoses were anterior uveitis in 62% ( n  = 21) followed by scleritis in 20% ( n  = 7). Only one patient had an episode of recurrent disease flare-up. All but one patient, who had concomitant C-ANCA seropositivity and granulomatosis with polyangiitis, had a favorable disease course with controlled inflammation using topical and/or systemic immunomodulatory therapy. Conclusion : In contrast to typical C-ANCA and P-ANCA, atypical P-ANCA seropositivity was not associated with severe vasculitis or poor prognosis in patients with the OID.